Teoria wolnodostępnej własności - Tittenbrun, Jacek (Wydział Prawa i Administracji UAM, 1996)
The property rights school advances as an argument the pros and cons of various forms of ownership the thepry of open accès property. According to the theory, a great disadvantage of common property is that it encourages its owners to exercise their ownership rights in ways that ignore the effects of their actions on others. However, its argument that a resource will be used inefficiently if acces is free is deficient since it fails to identify the real underlying cause of the "common pool" problem, which is not the form of ownership but the indivisibility of the saurce of supply On the other hand, the argument fails to distinguish between situations in which a resource is used for personal purposes only and those in which it is used for the purposes of obtaining income. It is only when the resource is udes for producing goods from which profit can be extracted that there exists an incentive to over-exploit the resource. From the theoretical point of view, the property rights theory errs in viewing exclusivity as the necessary feature of private ownership. For the private ownership to exist, it is sufficient that benefits are privately appropriated. It follows that the theory of free access property really applies competitive, individual, private ownership.
Theory of free-access property